Gender differences and similarities in aggression, suicidal behaviour, and psychiatric comorbidity in borderline personality disorder. (12th November 2018) - Sher, L.; Rutter, S. B.; New, A. S.; Siever, L. J.; Hazlett, E. A.
Abstract : Objective: We examined gender differences and similarities in aggression, impulsivity, suicidal behaviour, and psychiatric comorbidity in men and women with borderline personality disorder (BPD) compared with healthy controls. Method: A community sample of 511 participants (healthy controls: 81 men and 82 women; BPD patients: 145 men and 203 women) were rigorously characterized using structured diagnostic interviews and symptom severity assessments. Results: In comparison with women with BPD, men were less educated, had higher total Barratt Impulsivity Scale (BIS), BIS—motoric impulsiveness and BIS—non‐planning impulsiveness subscale, total Buss–Perry Aggression Questionnaire (BPAQ), and BPAQ—physical aggression subscale scores. Men with BPD were more likely to have comorbid narcissistic, antisocial, paranoid, and schizotypal personality disorders, alcohol and substance use disorders but less likely to have dependent and obsessive–compulsive personality disorders compared to women with BPD. There was a trend toward higher maximum lethality of suicide attempts in men suicide attempters compared with women suicide attempters but no difference between men and women with regard to the proportion of suicide attempters or the number of suicide attempts. Conclusion: Men with BPD are more impaired and may be at higher risk of dying by suicide compared to women with BPD.